THE IMPORTANCE OF MODERN TEACHING METHODS - Turdialiyeva Marjona Sherali qizi (Bright Mind Publishing, 2025)
In the context of the rapid transformation of the global information society, the use of modern teaching methods based on the integration of innovative technologies and pedagogical approaches is particularly important. Their implementation fosters a competency-based model of individual development focused on creativity, critical thinking, and self-education. In this article, we examine the role of interactive, project-based, and digital educational strategies as key factors in improving the quality of specialist training in a continuous education environment. Particular attention is paid to the synergy between traditional and innovative methods, as well as the impact of digitalization on the effectiveness of the educational process.
Keywords: Modern teaching methods, innovative technologies, competency-based approach, critical thinking, digitalization of education, interactive strategies, pedagogical innovations.